Una reinterpretación tímbrica del espacio eco-acústico: Improvisación guiada a través del análisis del paisaje sonoro (2023)
This work exposes a case study that uses the soundscape as an interpretive and analytical guide of space in the context of musical composition and improvisation. The article explores a methodology that allows organizing and interacting space as a compositional element. Different musicians participated in developing an intuitive analysis focused on the perception of space or sound events with moving trajectories. It was possible by using ambisonics technology, which allows it a more accurate appreciation of the acoustic characteristics of the space, as well as different moving acoustic events that occur during the recording. Artists like Barry Truax (Canada, 1947) and David Dunn (United States, 1953), who have included space in their works as an element to interact through sound. Both artists helped us as a reference in developing different strategies to interact with the space, using diverse sounds projected in the space. This methodology developed an approach to study soundscape, as well as showing the results obtained by the different members of the study. All this in order to incorporate the acoustic space as a musical element to study.